Preparation of a Salecan/poly(2‐acrylamido‐2‐methylpropanosulfonic acid‐co‐[2‐(methacryloxy)ethyl]trimethylammonium chloride) Semi‐IPN Hydrogel for Drug Delivery. (3rd January 2017) - Qi, Xiaoliang; Li, Junjian; Wei, Wei; Su, Ting; Zuo, Gancheng; Pan, Xihao; Zhang, Jianfa; Dong, Wei
Abstract: Salecan is a water‐soluble bacterial polysaccharide consisting of glucopyranosyl units linked by α‐1, 3 and β‐1, 3 glycosidic bonds. salecan is suitable for the development of hydrogels for biomedical applications, given its outstanding physicochemical and biological profiles. In this study we designed a new semi‐interpenetrating polymer network hydrogel that introduces the salecan polysaccharide into a stimuli‐responsive poly(2‐acrylamido‐2‐methylpropanosulfonic acid‐co‐[2‐(methacryloxy)ethyl]trimethylammonium chloride) (PAM) hydrogel matrix for controlled insulin release. We found that salecan not only tunes the structure and pore size of the PAM hydrogels, but also endows them with adjustable water release rates. More importantly, in vitro drug loading/release assays demonstrated that insulin is efficiently loaded into the resulting hydrogels and can be released in an on‐demand manner by controlling the pH and salecan dose. Furthermore, cell viability and cell adhesion experiments verified the cell compatibility of these hydrogel carriers. Together, these results make salecan‐incorporated PAM hydrogels promising materials for drug delivery. Abstract : Controlled release : We developed novel salecan‐containing semi‐interpenetrating polymer network (semi‐IPN) hydrogels for controlled drug release. On one hand, salecan was found to modify the architecture and pore size of the hydrogel network. On the other, salecan was observed to play a vital role in modulating the water content and the water release rate of the developing hydrogel, resulting in an adjustable drug release rate.